SUBSTRATOS A BASE DE TABACO E RESÍDUO INDUSTRIAL PARA PRODUÇÃO DE MUDAS DE PIMENTA - SANTOS, Benjamin Abel dos; BARBOSA, Bruno Rafael Simbre; LOVERA, Carlos Alberto; OLIVEIRA, João Paulo Zaluchi Souza de; BONFIM, Willian Gabriel Alves; ZOZ, Tiago (ANAIS DO ENIC, 2025)
-